Implementation of project-based learning for improve students' critical thinking skills in creative product and entrepreneurship subjects - Roza Febrianti; Yufrizal A; Randi Purnama Putra; Phonepasith Phongdala (Jurnal Pendidikan Teknologi Kejuruan, 2023)
The implementation of monotonous learning that lacks active student participation can contribute to the low critical thinking skills of students. This research aims to enhance students' critical thinking skills through the application of project-based learning (PjBL). The study evaluates the extent to which students' critical thinking skills can be improved through the implementation of PjBL. The research employs a Quasi-Experimental method. The study subjects consist of two groups: the experimental group, which utilizes the PjBL, and the control group, which follows a conventional model. Overall, after conducting prerequisite tests and hypothesis testing, a significant difference in critical thinking scores is observed between the experimental and control groups. Students are provided with the opportunity to exercise their critical thinking skills during the execution of project tasks. Consequently, it can be concluded that the PjBL model positively impacts the essential thinking abilities of 11th-grade machanical engineering students in creative products and entrepreneurship subject.